New Oxford spelling dictionary - Waite, Maurice (2014)
"The New Oxford Spelling Dictionary is the quick and reliable way to check spelling and word division. Spellings are based on the Oxford language research programme, the largest in the world. The Dictionary includes both primary (preferred) and secondary breaks for every suitable word - offering essential guidance for writers, editors, typesetters, and proofreaders needing to make reliable and consistent decisions relating to line endings" -- BOOK JACKET.
First edition published (as the Oxford Spelling Dictionary) 1986 -- Title page verso.
The New Oxford Spelling Dictionary replaces the second edition of the Oxford Spelling Dictionary -- Preface.
Variant title from front cover of dust jacket.
Keywords: English language -- Orthography and spelling -- Dictionaries; Anglais (Langue) -- Orthographe -- Dictionnaires; Spelling; Rechtschreibung